Investigation of the Stress Intensity Factor in Heterogeneous Materials Based on the Postprocessing Routine of Commercial Finite Element Software - Fengnan Guo; Yiming Li; Yufu Chen; Pengfei Liu; Xiaodong Wang (Applied Sciences)
An improved interaction integral method has been proposed for heterogeneous materials with complex interfaces based on the postprocessing routine of commercial finite element software. This approach introduces a suitably designed auxiliary field to eliminate the derivative terms of material parameters in the interaction integral, which enables the direct extraction of the stress intensity factor at the crack tip without considering the material interfaces. This paper utilizes the postprocessing routine of commercial finite element software to extract the simulation results from the specified analysis step to obtain the stress intensity factor. Validation via homogeneous material cases shows excellent agreement with the theoretical solutions. For two-dimensional/three-dimensional heterogeneous materials, the domain-independence of the present method still stands, even when the integral domain intersects interfaces. This new method improves the efficiency of parameter extraction and extends the scope of application of commercial finite element software for calculating the fracture parameters of heterogeneous materials.